2020
DOI: 10.1038/s41598-020-57551-4
|View full text |Cite
|
Sign up to set email alerts
|

A chronology of landsliding based on archaeological and documentary data: Pavlovské vrchy Hills, Western Carpathian Flysch Belt

Abstract: pavlovské vrchy Hills represent a distinctive elevation near the czech-Austrian border where the active, dormant and relict landslides cover 12% of the area. Here we focused on the chronology of landsliding in this area using geological, archaeological and historical evidence. The earliest records of landsliding were determined in locations underlying the dated archaeological settlements. The Upper Paleolithic settlement complex dated between 37-24 ka cal BP, was originally deposited over these landslides. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The oldest records were found in local chronicles and described landsliding in two villages (Jankovice and Košíky) in the close vicinity of Halenkovice in 1915. Bíl et al (2020) created an overview of the chronology of landsliding in the Pavlovské vrchy, an area at the Czech-Austria border belonging to the Western Carpathian Flysch Belt. They determined dates for 30 historical landslides.…”
Section: Systematic Work Describing Landslide Occurrence Based On Historical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The oldest records were found in local chronicles and described landsliding in two villages (Jankovice and Košíky) in the close vicinity of Halenkovice in 1915. Bíl et al (2020) created an overview of the chronology of landsliding in the Pavlovské vrchy, an area at the Czech-Austria border belonging to the Western Carpathian Flysch Belt. They determined dates for 30 historical landslides.…”
Section: Systematic Work Describing Landslide Occurrence Based On Historical Datamentioning
confidence: 99%
“…The number of these sources have been, however, subjected to academic scrutiny mostly in historical climatology and hydrology (Kjeldsen et al, 2014;Brázdil et al, 2018a). Similarly, Bíl et al (2020) combined different documentary and archaeological data to compile a chronology of landsliding in the Pavlovské vrchy (Czechia, OWC) and described the basic historical landslide terminology. The conceptual differences in hydrometeorological and geomorphologic hazards do not allow for uncritical transposition of the climatological insights into the historical landslide research and therefore call for new insights into the potential of the documentary data (Crozier and Glade, 1999;Raška et al, 2014b).…”
Section: Data Availabilitymentioning
confidence: 99%
“…Raška et al (2015) analysed historical landslides in two Czech regions and found seven different terms referring to landslides and three for rockfalls. In total, five German different terms were used to describe the landslides in the Pavlovské vrchy Hills (OWC) between the middle of the seventeenth-twentieth centuries (Bíl et al, 2020).…”
Section: Limitations Of the Childa Databasementioning
confidence: 99%
“…The availability of sources also displays a distinct geographical variation due to different historical developments in individual regions. Several smaller uncertainties related to historical landslides have thus appeared, e.g., a lack of narrative sources before 1920 and in the Czech border areas after 1945 (Bíl et al, 2020) or difficulties with recognition of landslides and scoured slopes during the floods in early documentary records. As regards the Czech border areas, chronicles were lost or carried away mainly by German inhabitants displaced after 1945.…”
Section: Limitations Of the Childa Databasementioning
confidence: 99%
See 1 more Smart Citation